Numerical Simulation of The Influence of Geometric Parameter on The Flow Behavior in a Solar Chimney Power Plant System (Journal of Engineering, 2014)
Numerical simulations have been carried out on the solar chimney power plant systems. This paper gives the flow field analysis for a solar chimney power generation project located in Baghdad. The continuity, Naver-stockes, energy and radiation transfer equations have been solved and carried out by Fluent software. The governing equations are solved for incompressible, 3-D, steady state, turbulent is approximated by a standard k -  model with Boussiuesq approximation to study and evaluate the performance of solar chimney power plant in Baghdad city of Iraq. The different geometric parameters of project are assumed such as collector diameter and chimney height at different working conditions of solar radiation intensity (300,450,600,750 and 900 W/m2) to gain the optimal designed structure. The results show that the change of collector diameter and chimney height has considerable effects on the performance of the system. The velocity increase when the collector diameter and chimney height increase and reach to the maximize value at H=D 12 m and when solar intensity (900 W/m2). The study shows that Iraqi weather are suitable for this system.